2016
DOI: 10.1111/1744-9987.12475
|View full text |Cite
|
Sign up to set email alerts
|

Online Hemodiafiltration Reduces Bisphenol A Levels

Abstract: Several uremic toxins have been identified and related to higher rates of morbidity and mortality in dialysis patients. Bisphenol A (BPA) accumulates in patients with chronic kidney disease. The aim of this study is to demonstrate the usefulness of online hemodiafiltration (OL-HDF) in reducing BPA levels. Thirty stable hemodialysis patients were selected to participate in this paired study. During three periods of 3 weeks each, patients were switched from high-flux hemodialysis (HF-HD) to OL-HDF, and back to H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…The decrease of 72% in BPA levels during the first OL-HDF session when the switch membranes were BPA-free membranes is larger than expected for a protein-bound molecule. However, it is consistent with results from Quiroga et al who observed an average reduction of 45% when dialyzers with and without BPA were analyzed as a single group [ 12 ]. This is consistent with a 72% reduction with BPA-free membranes and no change with BPA-containing membranes in our study (the mean of a 72% reduction with BPA free membranes and a 1% with BPA containing membranes is a 36% reduction, in the range of the 45% observed by Quiroga et al).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The decrease of 72% in BPA levels during the first OL-HDF session when the switch membranes were BPA-free membranes is larger than expected for a protein-bound molecule. However, it is consistent with results from Quiroga et al who observed an average reduction of 45% when dialyzers with and without BPA were analyzed as a single group [ 12 ]. This is consistent with a 72% reduction with BPA-free membranes and no change with BPA-containing membranes in our study (the mean of a 72% reduction with BPA free membranes and a 1% with BPA containing membranes is a 36% reduction, in the range of the 45% observed by Quiroga et al).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, BPA levels were higher in the 69 patients in the hemodialysis study (64.55±93.8 ng/ml) [ 7 ] and also in the 18 patients in the hemodialysis study that went on to be enrolled in the present study (98.96±120.75 ng/ml) than in the patients treated for longer than 6 months with OL-HDF (23.42±3.81 ng/mL). The data support the concept advanced by Quiroga et al [ 12 ], that he dialysis technique (OL-FDF vs hemodialysis) indeed results in lower BPA levels. The BPA concentration range differed in both studies, probably due to the use of a different BPA assay, to individual patient or dialysis characteristics, to different duration of the study or to the existence of limitations to BPA clearance such as continuous leakage from dialyzer membranes (in the prior studies both BPA-containing and BPA-free membranes were grouped together).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…After carefully studying the text, ten publications were selected 1 . Of these, only 1 quantifies the urinary BPA concentration in dialysis patients [60] and 9 in serum [15,[60][61][62][63][64][65][66][67][68].…”
Section: Systematic Review Of Bpa Exposure In Hemodialysis Patientsmentioning
confidence: 99%
“…Hence, the metabolism, tissue distribution, and elimination from the body remains unclear and no-TDI has been established for these compounds. Recent studies affirm that OL-HDF could reduce BPA blood levels in dialyzed patients [42,43]. However, the methodology used raises some questions since the number of patients was low, and some issues regarding the analytical method used.…”
Section: Discussionmentioning
confidence: 99%